Exploring the inhibitory mechanism of p-coumaric acid on α-amylase via multi-spectroscopic analysis, enzymatic inhibition assay and molecular docking. (May 2023) - Huang, Yanyi; Condict, Lloyd; Richardson, Samantha J.; Brennan, Charles Stephen; Kasapis, Stefan
Abstract: The impact of p-coumaric acid (p-CA) on α-amylase activity was investigated through multi-spectroscopic methods, enzymatic assays and molecular docking. UV–vis analysis suggests that the α-amylase-p-CA complex is stabilised by non-covalent bonds, with molecular docking suggesting that hydrogen bonding, π-π stacking interactions and Van Der Waals forces are mainly responsible for ligand stabilisation within the active site of α-amylase. Fourier transform infrared (FTIR) and circular dichroism (CD) spectra showed that complex formation induced a reduction of α-helix and β-sheet components in α-amylase, while enhancing disordered structures. Fluorescence quenching and Job plot results argue for significant interactions between α-amylase and p-CA, yielding a binding affinity of 2.57 × 10 4  M −1 and a 1:1 binding stoichiometry. Thermostability of α-amylase was also impacted upon complexation, with increasing concentrations of p-CA reducing the thermal stability of α-amylase. p-CA showed a competitive inhibitory action on α-amylase activity, with the IC50 value calculated to be 3.09 mM, which is comparable to the 2.03 mM of the acarbose positive control. The findings provide a theoretical basis for potential application of p-CA in functional foods or as a nutraceutical. Graphical abstract: Image 1 Highlights: p-Coumaric acid competitively bound to the active site of α-amylase. Binding of p-coumaric acid induced conformational alterations to α-amylase. Thermal stability of α-amylase was reduced upon complexation with p-coumaric acid. 1:1 Binding stoichiometry was observed for the α-amylase-p-coumaric acid complex.